STEAM EDUCATION TECHNOLOGY CONTENT IN PRIMARY EDUCATION (International journal of artificial intelligence, 2025)
This article analyzes the theoretical foundations and practical importance of STEAM (Science, Technology, Engineering, Art, Mathematics) educational technology in primary education. The STEAM approach has been shown to develop children's creativity, critical thinking, collaboration and problem-solving skills through the integration of science, technology, engineering, art and mathematics. The article examines the advantages of implementing STEAM in elementary schools, the problems that arise, and ways to overcome them.